Platycodon grandiflorus polysaccharides deeply participate in the anti-chronic bronchitis effects of platycodon grandiflorus decoction, a representative of “the lung and intestine are related” - Liu, Yang; Chen, Qingqing; Ren, Rongrong; Zhang, Qingqing; Yan, Guiming; Yin, Dengke; Zhang, Mingyan; Yang, Ye (Frontiers in Pharmacology, 2022)
Platycodon grandiflorus (Jacq.) A.DC. (PG) root is one of the most commonly used medicine-food materials for respiratory discomfort in Asia, usually in the form of a decoction or leaching solution. As everyone knows, both of decoction and leaching solution is a polyphase dispersion system, containing low-molecular-weight water-soluble active ingredients and hydrophilic macromolecules. This study aimed to discuss the synergistic effect of Platycodon grandiflorus polysaccharide (PGP) and platycodin D (PD) in PG decoction against chronic bronchitis (CB) and the mechanism underlying. A series of PGP, PD, and PGD + PD suspensions were administrated to CB model rats, on the levels of whole animal and in situ intestinal segment with or without mesenteric lymphatic vessels ligation. It exhibited that PGP exhibited synergistic effects with PD, on improving the histopathological abnormity, mucus secretion excess, and immunological imbalance in lung of CB model rat, closely associated with its modulations on the mucosal immunity status in small intestine. The polysaccharide macromolecules in PG decoction or leaching solution should be responsible for the modulation of pulmonary immune state, possibly through the common mucosal immune between small intestine and lung. These results might be a new perspective that illustrates the classical theory of “the lung and intestine are related” in traditional Chinese medicine.